Critique and Reinterpretation of Misogynistic Hadith: An Analysis of Islamic Justice and a Gender Perspective - Andi Bangsawan Tolere; Abdul Rahman Sakka; La Ode Ismail Ahmad (Global Writing Academica Researching and Publishing, 2026)
This article aims to reexamine hadiths that are often perceived as misogynistic through the lens of Islamic justice and a gender perspective. The main focus of this study is two hadiths in Sahih al-Bukhari, namely hadith number 304 concerning women being described as “deficient in intellect and religion”, and hadith number 7099 regarding female leadership. This research employs a qualitative method with a library research approach, along with thematic hadith analysis (maudhu’i). The data are analyzed by referring to classical commentaries, particularly Fath al-Bari by Ibn Hajar al-Asqalani, in order to understand the historical context and substantive meaning of the hadiths. The findings indicate that a purely textual understanding of these hadiths has the potential to generate gender bias, however, through contextual and interpretive approaches, it is found that the meanings of the hadiths do not contradict the principles of justice in Islam. Therefore, reinterpretation becomes essential to present a more proportional, contextual, and relevant understanding in line with contemporary gender discourse without neglecting the authority of the Islamic scholarly tradition. In addition, this study emphasizes the importance of integrating classical and contemporary approaches as a methodological effort to avoid distortion of meaning and to strengthen the relevance of hadith studies in addressing modern social issues.